Pengaruh Kualitas Produk, Harga dan Keputusan Pembelian Pakaian Bekas Thrifting - Ardrarani, Gevana Ardrarani; Rachmawati, Lucky (Jurnal Ekonomika : INDEPENDEN, 2023)
According to kotler and keller (2016), it is consumer behavior to observe how Individuals or groups choose, buy, use and how goods, services, ideas or experiences meet their needs and activities. The purpose of this study is to know how the influence of quality, price and brand image on the decision to buy cheap used clothes in Surabaya. The research method that used in this study is the quantitative method with a descriptive analytical analysis using linear regression analysis using the results that variable product quality, price and brand image affect both partial and simultaneous overclothing purchase decisions in surabaya